2015
DOI: 10.1515/biolog-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to oxidative stress in Zea mays roots under short-term Pb2+ exposure

Abstract: Lead (Pb), a widespread contaminant in terrestrial landscape, is highly detrimental to plant and animal life. Specifically, Pb-contaminated soils cause a sharp decrease in crop productivity, thereby posing a serious risk to agriculture. A study was planned to investigate the toxic effect of Pb 2+ (0, 16, 40 and 80 mg L −1 ) in the seedlings of maize (Zea mays), in terms of induced physiological and biochemical changes at initial hours of treatment (0-8 h). Increased accumulation of malondialdehyde (MDA) served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…CAT activity was determined by monitoring the disappearance of H 2 O 2 at 240 nm and calculated using ε = 39.4 mM −1 cm −1 [ 22 ]. APX activity was determined as the oxidation of ascorbic acid at 290 nm and calculated using ε = 2.8 mM −1 cm −1 [ 3 ]. GPX activity was determined at 470 nm in terms of guaiacol oxidized and calculated using ε = 26.6 mM −1 cm −1 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAT activity was determined by monitoring the disappearance of H 2 O 2 at 240 nm and calculated using ε = 39.4 mM −1 cm −1 [ 22 ]. APX activity was determined as the oxidation of ascorbic acid at 290 nm and calculated using ε = 2.8 mM −1 cm −1 [ 3 ]. GPX activity was determined at 470 nm in terms of guaiacol oxidized and calculated using ε = 26.6 mM −1 cm −1 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The phytotoxic effects of heavy metals have been attributed to pro-oxidative effects of metal ions, that disrupt various physiological and biochemical processes [ 2 ]. Lead (Pb) has been reported to induce reactive oxygen species (ROS) generation and alter enzymatic machinery in lupin roots, pea root cells, rice plants, maize roots, and aquatic plants such as Wolffia arrhiza and Elodea canadensis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lead induced oxidative stress is reported to produce reactive oxygen species (ROS) in plants [146,147]. These ROS synthesized as a result of oxidative stress in plants can cause deleterious effects such as lipid peroxidation, disrupted cell membrane, DNA and protein damage, inhibition of photosynthesis, and inhibition of ATP production [148].…”
Section: Mechanistic Understanding Of Pb Toxicity and Tolerance In Plmentioning
confidence: 99%
“…Researchers observed that NO significantly reduced the negative impact of Pb toxicity in the form of oxidative stress induced by ROS (malondialdehyde, conjugated dienes, hydroxyl ions and superoxide anion). Furthermore, exogenous NO interferes ROS detoxification mechanism and enhances the antioxidant enzyme activity in wheat roots ( Kaur et al, 2015a ). Based on the above results, eco-remediation technologies are therefore primarily applicable in the field of wet land agriculture.…”
Section: Phyto-managementmentioning
confidence: 99%